2020
DOI: 10.9770/jesi.2020.7.3(50)
|View full text |Cite
|
Sign up to set email alerts
|

Health tourism in low mountains: a case study

Abstract: Health tourism is a specific type of tourism with great prospects. Most people do not have time for long trips, but there is a great need for a change of scenery and restoration of strength. There are many examples when in the regions in order to improve health and relaxation, nearby areas are being developed. It is most promising to create programs for such tourism near existing resorts that have the necessary infrastructure and medical facilities, while individual client requests must be taken into account. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…Popular destinations for such tourists often include attractions such as mountains, lakes, rivers, beaches, and forests, all of which are natural resources that promote the improvement of wellness and are, therefore, ideal for the development and sustainability of health and wellness tourism [13]. Though many people may not have time for long trips, relaxation and a change of scenery are often all that are needed [14]. For example, Dunets et al (2020) reported that the resort town of Belokurikha, Russia, which is located in the foothills of the Altai mountains, has excellent opportunities for development as a health and wellness destination, as indicated by tourists' overall satisfaction and desire to visit [14].…”
Section: Heath Tourism Emerging In Chinese Mountainous Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular destinations for such tourists often include attractions such as mountains, lakes, rivers, beaches, and forests, all of which are natural resources that promote the improvement of wellness and are, therefore, ideal for the development and sustainability of health and wellness tourism [13]. Though many people may not have time for long trips, relaxation and a change of scenery are often all that are needed [14]. For example, Dunets et al (2020) reported that the resort town of Belokurikha, Russia, which is located in the foothills of the Altai mountains, has excellent opportunities for development as a health and wellness destination, as indicated by tourists' overall satisfaction and desire to visit [14].…”
Section: Heath Tourism Emerging In Chinese Mountainous Areasmentioning
confidence: 99%
“…Though many people may not have time for long trips, relaxation and a change of scenery are often all that are needed [14]. For example, Dunets et al (2020) reported that the resort town of Belokurikha, Russia, which is located in the foothills of the Altai mountains, has excellent opportunities for development as a health and wellness destination, as indicated by tourists' overall satisfaction and desire to visit [14]. Kling et al (2020) found that spending time in mountainous areas was linked to better health and well-being [15].…”
Section: Heath Tourism Emerging In Chinese Mountainous Areasmentioning
confidence: 99%
“…At the same time, an increase in the state's share in the formation of the national health care system, in the absence of effective management tools (a process-oriented approach to managing a medical organization, the introduction of lean technologies in the workplace) and control (independent trade unions, associations, etc.) leads to monopolization of the market for medical servants and the destruction of competitive relationships (Zaripova et al, 2019;Dunets et al, 2020;Bukharina et al, 2014;Kuzmin et al, 2018). The lack of competition in the medical services market is detrimental both to health workers and, of course, to patients.…”
Section: Implementing the Patient-oriented Approachmentioning
confidence: 99%
“…Against the background of unconditional improvement in the performance of almost all areas of the economy in which digital assets are increasingly used, therefore, a number of problems arise that need to be resolved in a timely manner. Nowadays, Russia also faces the challenge of creating a new management model based on digital technologies developed by domestic scientists and practitioners, as well as ensuring transparent processes for their implementation (1)(2)(3). At the same time, according to leading economists, constructing a new economic model while maintaining the existing type of economic development is not possible, since there are growth limits due to the limitations of traditional factors of production.…”
Section: Introductionmentioning
confidence: 99%